Regulating China's health code system to prepare for future pandemics - Shen, Taixia; Wang, Chao (Frontiers in Public Health, 2023)
This study investigates the challenges that China's health code system presents to individuals' lives and social development, using normative analysis and a case study. It looks for effective strategies to reform and regulate this system to prepare for future pandemics. Health code apps and mini programs have been widely deployed as effective tools for COVID-19 containment in China. However, their widespread and improper use has created risks due to the lack of both a systematic design and a basic supervision mechanism. The health code system risks infringing on individual privacy during data collection and storage. During the pandemic, the right to liberty and the right to treatment of Chinese citizens who lacked an appropriate health code were severely compromised. In some instances, the health code system was used as a stability maintenance tool by the authorities through arbitrary health code conversions. This article argues that China's health code systems should be reformed and regulated in preparation for future pandemics and that a new act regulating its management and use should be launched at the national level. Data collection, retention, and processing should be limited to the minimum amount of data needed to achieve the objective of protecting public health. The health code conversion power wielded by the authorities should be defined and regulated, the rules and procedures of code conversion should be transparent, arbitrary health code conversion behaviors should be prevented and punished, and persons whose rights have been violated by wrongful code conversion should have access to legal remedies.